2019
DOI: 10.1101/724906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topology-Dependent Interference of Circuit Function by Growth Feedback

Abstract: Growth-mediated feedback between synthetic gene circuits and host organisms leads to diverse emerged behaviors, including growth bistability and enhanced ultrasensitivity. However, the range of possible impacts of growth feedback on different gene circuits remains underexplored. Here, we mathematically and experimentally demonstrated that growth feedback affects the functions of memory gene circuits in a network topology-dependent way. Specifically, the memory of the self-activation circuit is quickly lost due… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 54 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…Unexpected Oscillatory Dynamics Induced by Growth Feedback with Varied Nutrition Level. In our previous work, 19 we built a simple synthetic self-activation (SA) gene circuit (Figure 1A), in which the transcription factor AraC activates the expression of itself by binding to its promoter P BAD . Reporter gene green fluorescent protein (GFP) was used to visualize the dynamics of AraC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unexpected Oscillatory Dynamics Induced by Growth Feedback with Varied Nutrition Level. In our previous work, 19 we built a simple synthetic self-activation (SA) gene circuit (Figure 1A), in which the transcription factor AraC activates the expression of itself by binding to its promoter P BAD . Reporter gene green fluorescent protein (GFP) was used to visualize the dynamics of AraC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, we found that the circuit did not exhibit hysteresis even as a stable bimodal distribution was observed. 19 The underlying reason is that the gene circuits interact with the host cell growth (Figure 1A), which led to the loss of memory for the self-activation circuit after diluting the activated cells into the fresh 100% Lysogeny broth (LB) rich medium. 19 The memory can be maintained well with the M9 minimal culture low-nutrient (0% LB) medium.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies have also revealed gaps in our understanding of how bacteria integrate temporally and spatially heterogeneous signals into beneficial phenotypic changes (Kandemir et al, 2018;Sanfilippo et al, 2019). There have been explorations of the connections between spatial structure and information processing in microbial colonies (Alnahhas et al, 2019;Bittihn et al, 2020;Dal Co et al, 2020;Gupta et al, 2020;Kong et al, 2017;Kussell and Leibler, 2005;van Vliet et al, 2018;Zhang et al, 2021), but these studies have not addressed the information processing of microbes embedded in three-dimensional synthetic materials. Along this line, studies using engineered cells suggest that phenomena like Turing patterns may facilitate collective decision-making based on spatial and temporal information (Cao et al, 2016;Karig et al, 2018).…”
Section: Introductionmentioning
confidence: 99%